2004
DOI: 10.1097/00042737-200406000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German version of the Chronic Liver Disease Questionnaire

Abstract: The CLDQ-D is well accepted by patients with chronic liver diseases and has good reliability and satisfactory discriminant validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
56
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 21 publications
15
56
0
3
Order By: Relevance
“…Figure 1 compares the distribution of the Chinese (HK) CLDQ scores with those from other countries. The distribution pattern of the Chinese (HK) CLDQ subscale scores was very similar to those of other countries [3,9,11,13] , except Italy, supporting cross-cultural conceptual equivalence. Table 3 shows the mean item scores and standard deviation of the 29 CLDQ items grouped under their hypothesized subscales.…”
Section: Subjectsmentioning
confidence: 65%
See 1 more Smart Citation
“…Figure 1 compares the distribution of the Chinese (HK) CLDQ scores with those from other countries. The distribution pattern of the Chinese (HK) CLDQ subscale scores was very similar to those of other countries [3,9,11,13] , except Italy, supporting cross-cultural conceptual equivalence. Table 3 shows the mean item scores and standard deviation of the 29 CLDQ items grouped under their hypothesized subscales.…”
Section: Subjectsmentioning
confidence: 65%
“…Previous studies showed that the CLDQ is more responsive than a generic measure to detect a change in patients with CLD [3,9] . It has been translated and validated in different languages [9][10][11][12][13] , supporting its potential for crosscultural adaptation. However, most of the psychometric data of the CLDQ have been derived from patients with hepatitis C virus (HCV) infection and Western populations.…”
Section: Introductionmentioning
confidence: 99%
“…Качество жизни (КЖ) оценивали по опрос-нику для пациентов с ХЗП -CLDQ (The chronic liver disease questionnaire) [10,24].…”
Section: дизайн исследованияunclassified
“…Ответ респондентов включает 7 возможных вариантов: от «постоянно» до «никогда». Чем выше суммарный показатель опросника, тем более высокий уровень КЖ у пациента [10,24]. Достоверное улучшение КЖ получено в группе пациентов на комбинированной схеме лекарственных средств.…”
Section: результаты исследования и обсуждениеunclassified
“…[4][5][6] It has been translated and validated into various languages all over the world including both European (German, 7 Spanish, 8 Italian, 9 Swedish,…”
Section: Introductionmentioning
confidence: 99%